2013
DOI: 10.1063/1.4773542
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of K0.5Na0.5NbO3 thin films grown on Nb:SrTiO3 single-crystalline substrates with different crystallographic orientations

Abstract: To attain a deep understanding of ferroelectric and piezoelectric characteristics of K0.5Na0.5NbO3 as a promising lead-free compound, the ferroelectric and piezoelectric responses of its epitaxially grown films with three primary orientations of [001], [110], and [111] were investigated with an emphasis on the influence of crystallographic orientation. The films were prepared by sol-gel processing using Nb-doped SrTiO3 single-crystalline substrates with various cutting directions. A peak remnant polarization v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 33 publications
3
48
1
Order By: Relevance
“…5,6 Previous studies revealed that KNN films with high phase purity could be synthesized by a sol-gel process on Pt/Ti/SiO 2 /Si substrates or perovskite oxides like single-crystalline SrTiO 3 (abbreviated as STO) wafer. 7,8 Even though it is possible to prepare oriented KNN films on Pt/Ti/SiO 2 /Si substrates, epitaxial ones grown on STO substrates are more attractive not only due to their outstanding performance but also because the specimens are ideal for structural investigation. Such studies are particularly necessary for the KNN-based system, which has a more complicated phase structure than the well-studied Pb(Zr,Ti)O 3 (abbreviated as PZT) counterpart.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Previous studies revealed that KNN films with high phase purity could be synthesized by a sol-gel process on Pt/Ti/SiO 2 /Si substrates or perovskite oxides like single-crystalline SrTiO 3 (abbreviated as STO) wafer. 7,8 Even though it is possible to prepare oriented KNN films on Pt/Ti/SiO 2 /Si substrates, epitaxial ones grown on STO substrates are more attractive not only due to their outstanding performance but also because the specimens are ideal for structural investigation. Such studies are particularly necessary for the KNN-based system, which has a more complicated phase structure than the well-studied Pb(Zr,Ti)O 3 (abbreviated as PZT) counterpart.…”
mentioning
confidence: 99%
“…Our previous study showed that epitaxial KNN films grown on the (100) surface of STO substrates possess higher piezoelectric property than the counterparts on the (110) and (111) surfaces, which could not be fully understood by the knowledge of spontaneous polarization and domain configuration. 8 It is known that PZT-based films grown on SrTiO 3 (100) surfaces are [001] oriented with an out-of-plane direction as c-axis. 11 However, more detailed studies are needed to investigate the precise crystallographic structure of KNN films on cubic substrates because of the lattice parameter differences existing between KNN and PZT systems.…”
mentioning
confidence: 99%
“…However, the ferroelectric phase is subject to varying degrees of intrinsic and/or extrinsic influences, ranging from elemental composition, 9 annealing, growth technique, 10 and straining, 11 among others. [12][13][14][15][16] Therefore, it is important to understand the quality of perovskites in terms of their demonstrated ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, implies that KNN films are coherently in-plane oriented. Similar behaviour has been reported when preparing KNN thin films by sol-gel processing using STO(100) as substrate [23]. In addition, the rocking curves or ω-scan, Figure 3b, of the pure KNN(70/70) films deposited onto STO(100) were performed using the (400) reflection, 2θ = 100.8 º.…”
Section: Figure 2 Xrd Patterns Of Knn (A) and Knn-la (B) Thin Films mentioning
confidence: 72%